Investigation of Formation and Dissociation Mechanisms of Pure and Mixed CO2 Hydrates in the Presence of Thermodynamic and Kinetic Promoters using Molecular Dynamics Simulation - Sinehbaghizadeh, Saied (Curtin University, 2023)
CO2 hydrates as non-flammable solid compounds would contribute to many industrial processes. Toward developing substantial applications of CO2 hydrates, molecular dynamics (MD) simulations can aid to understand their characteristics and mechanisms involved so that complete the laboratory experimental results at a macroscopic level. In this regard, understanding the promotion mechanisms of promoters on the hydrate formation and dissociation at the molecular level would assist in either establishing feasible processes or finding more efficient promoters.